Effect of added sulphur dioxide levels on the fermentation characteristics of strawberry wine. Issue 3 (25th July 2016) - Sun, Yumei; Zhang, Ting; Lü, Huiwei; Yu, Zhimin; Li, Xianzhen
Abstract : The aim of this study to evaluate the effects of sulphur dioxide (SO2 ) on strawberry wine fermentation and on the quality of the final wine product. Major aroma compounds, reducing sugars, ethanol, titratable acid and microflora were analyzed during the fermentation of strawberry wine supplemented with 0–100 mg/L SO2 . As the amount of added SO2 increased, the consumption of reducing sugars and soluble solids and ethanol production decreased during early fermentation, but increased during late fermentation. During the fermentation process, the concentrations of 2‐phenethanol, isobutanol and isopentanol significantly increased and those of n ‐propanol, isoamyl acetate and ethyl lactate decreased with increasing amount of added SO2 . The production of n ‐butanol, ethyl acetate and ethyl butyrate was slightly dependent on the amount of added SO2 . Yeast cells were the dominant microbe in the fermenting strawberry pulp, and indigenous bacteria and fungi populations decreased rapidly or disappeared because of their sensitivity to SO2 . It was concluded that 60–80 mg/L SO2 should be added during strawberry wine fermentations to improve wine quality. Copyright © 2016 The Institute of Brewing & Distilling